Key takeaways from IWMI’s participation at the first-ever MENA Climate Week - International Water Management Institute (International Water Management Institute, 2022)
The blog is on the Q&A discussion by Vidhisha Samarasekara, IWMI’s Strategic Program Director for Water, Climate Change, and Resilience, at the MENA Climate Week. In this Q&A, she discusses the conference’s influence in shaping the agenda for the upcoming COP27 climate summit and highlights some of the ways IWMI is strengthening water security across the region so that the countries of the Middle East and North Africa may become more resilient in the face of climate change.